Symmetry of viscosity solutions for fully nonlinear parabolic equations. (June 2016) - Dai, Limei
Abstract: In this paper, we study the symmetry of viscosity solutions for fully nonlinear parabolic equations − u t + F ( x, t, u, D u, D 2 u ) = 0 . We first establish the maximum principles of viscosity solutions for linear parabolic equations. Then the symmetry and monotonicity results of viscosity solutions for fully nonlinear parabolic equations in a bounded domain and a punctured cylinder are proved.